Chemosensory characterization of virgin olive oils obtained from organic and conventional practices during fruit ripening. (29th May 2017) - Jiménez, Brígida; Rivas, Ana; Lorenzo, María Luisa; Sánchez‐Ortiz, Araceli
Abstract: The current increase in demand for organic products by consumers, including virgin olive oils (VOO), makes it necessary to study the characteristics of these types of foods. Moreover, the higher quality of organic products versus that of conventional products is controversial. In this regard, the chemosensory qualities of several virgin olive oils produced from fruit grown in an experimental orchard at four different stages of maturation under organic and conventional management systems were analysed. The resulting oils were subjected to sensory and chemical analyses. According to the data organic virgin olive oils showed higher concentrations of volatile compounds synthesized throughout lipoxygenase (LOX) pathway, responsible for green grass and olive fruity sensory attributes and showed lower concentrations of phenols, related to bitter and pungent attributes. Sensorily, conventional oils were more bitter and richer in green‐leaf character, while organic oils were sweeter. Multivariate analysis showed that 10 sensory descriptors and 6 compositional parameters clearly discriminate between Picual and Hojiblanca cultivars and between organic and conventional samples. These results could be useful to clarify the different sensory characteristic between virgin olive oils obtained by conventional and organic olive crops. Abstract : Effect of agronomic practices: organic vs. conventional management on sensory test, phenolic and volatile compounds were analyzed in 'Picual' and 'Hojiblanca'cultivars at different ripening stages. A multivariate analysis was applied to the sensory and chemical characterization of the oils. The results suggest that agronomical practices and fruit ripening, may affect the sensory profiles of the virgin olive oils.